ISSUES OF MANAGING RISKS IN INDONESIAN BANKS DURING COVID-19 PANDEMIC CRISIS - Pranoto Effendi (STIE PGRI Dewantara Jombang, 2021)
The Covid-19 pandemic has had a substantial negative impact on the banking sector in Indonesia. The purpose of this study is to survey various initiatives and measures by the Indonesian banks and the financial authority organization to alleviate and anticipate this impact. This research employs simple qualitative analysis, which aims to identify issues pertinent to risk management activities by the Indonesian Financial Authority and the banks in preparing for the worst scenario. Data used in this study are news articles taken from Republika Newspaper website. The result shows that the Indonesian Authority and its banks take various actions and plans, which are crucial in managing the banks to survive the pandemic crisis. The pandemic also has brought changes to the landscape of the Indonesian financial industry in a better way to manage risks to prepare for a similar crisis in the future.